Poetics of the Soul: Art and Consciousness for the 21st Century - Soares, Paula (2008)
The Poetics of the Soul model is the result of a PhD thesis based on the reflection and (re)location of the Mission of Art and the Creative Process on a New Millennium basis. Its roots lead to the (re)integration of the Creator, the Mirror-work of Art and the Perceptor in a dynamic molecular structure.